2019
DOI: 10.1136/bmjnph-2018-000011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 2-hour interval between dinner and bedtime on glycated haemoglobin levels in middle-aged and elderly Japanese people: a longitudinal analysis of 3-year health check-up data

Abstract: IntroductionThere is a need for evidence-based measures to examine the risk factors for lifestyle-related diseases. In Japan, a 2-hour interval between dinner and sleep is recommended as a healthy practice. However, the effect of an appropriate duration between dinner and bedtime on glycated haemoglobin (HbA1c) levels remains unclear. This study aimed to identify the effect of a duration of 2 hours or shorter between dinner and bedtime on HbA1c levels in middle-aged and elderly Japanese individuals.MethodsA lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…3), energy loading towards the latter half of the day, and a longer interval between time of last meal and bedtime. These findings are of relevance as there are epidemiological data that show an association between breakfast skipping and/or late meals and cardiometabolic health (1) , although the relationship of interval between time of last meal and bedtime on health outcomes has not been well studied (75) . Importantly, these temporal aspects of eating may all be measured using a single method the actual timing of meals (clock time), rather than patterns of meal skipping, or intervals relative to wake or sleep times.…”
Section: Temporal Patterns Of Eating Amongst Chronotypes: Implication...mentioning
confidence: 83%
“…3), energy loading towards the latter half of the day, and a longer interval between time of last meal and bedtime. These findings are of relevance as there are epidemiological data that show an association between breakfast skipping and/or late meals and cardiometabolic health (1) , although the relationship of interval between time of last meal and bedtime on health outcomes has not been well studied (75) . Importantly, these temporal aspects of eating may all be measured using a single method the actual timing of meals (clock time), rather than patterns of meal skipping, or intervals relative to wake or sleep times.…”
Section: Temporal Patterns Of Eating Amongst Chronotypes: Implication...mentioning
confidence: 83%
“…Higher food intake closer to bedtime has also been known to have a negative effect on sleep quality. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] found that evening eating did contribute to weight gain and metabolic dysfunction, regardless of calorie intake. However, a study by Maw and Haga [ 24 ] found that in middle-aged and elderly Japanese persons, 2-h or shorter intervals between dinner and night did not affect HbA1C alterations. To sustain stable HbA1C patterns, the focus should be on maintaining a normal BMI value and refraining from smoking and consuming alcohol in the long run.…”
Section: Discussionmentioning
confidence: 99%